STEM education 2.0 : Myths and truths - What has K-12 STEM education research taught us? - Sahin, Alpaslan; Mohr-Schroeder, Margaret J. (Koninklijke Brill, 2019)
STEM Education 2.0' discusses the most recent research on important selected K-12 STEM topics by synthesizing previous research and offering new research questions. The contributions range from analysis of key STEM issues that have been studied for more than two decades to topics that have more recently became popular, such as maker space and robotics. In each chapter, nationally and internationally known STEM experts review key literature in the field, share findings of their own research with its implications for K-12 STEM education, and finally offer future research areas and questions in the respected area they have been studying. This volume provides diverse and leading voices in the future of STEM education and STEM education research.